O caminho-de-ferro de Benguela 1e o impacto económico, social e cultural na sua zona de influência (1902-1952) - Esteves, Ernmanuel (Africana Studia, 2020)
This article studies the politicai, economic and social changes caused by Bengela railway in the center and south of Angola.